Evaluation of Antinociceptive Activity of Berberis Vulgaris L. Fruit’s Hydroethanolic Extract in Male Mice: Antinociceptive activity of Berberis vulgaris in male mice - Naser Mirazi,; Abdolkarim Hosseini, (Iranian Journal of Pharmaceutical Sciences, 2013)
Herbal medicine has an old history with a broad application all over the world. Many researches have focused on the curative as well as antinociceptive effects of herbal extract. The aim of this study was to investigate the analgesic effects of Berberis vulgaris hydroethanolic extract (BVE) in male mice. 30 male mice were divided into 5 groups: control, treated by morphine, treated by BVE (150 & 300 mg/kg) and naloxane plus BVE (300 mg/kg) randomly. To assess the antinociceptive effects of BVE, the animals were examined by employing different pain models such as, tail-flick tests (for acute pain) and acetic acid-induced writhing (for chronic pain) after treatment with morphine, naloxane and BVE. The results indicate that the BVE showed an important antinociceptive effect at doses of 150 and 300 mg/kg (P<0.01 and P<0.001, respectively), administered intraperitoneally in mice, which significantly inhibited the abdominal constrictions (55.73% of inhibition) induced by acetic acid and increase tail-flick latency when compared to control group in the same dose, although they were less effective than morphine in the same assay. The antinociceptive models employed here reveal a potential analgesic effect of the Berberis vulgaris hydroethanolic extract. We suggest that this effect might be caused by anti-inflammatory effect and the stimulation of the opioid receptors.